An Analysis And Evaluation Of Construction Waste On Structural Construction In Grand Sungkono Langoon Project By Using Pareto Method And Fishbone Diagram - Salim Syarief (Journal of World Conference (JWC), 2020)
In a construction project, there must be construction waste. The present study aims to find out the quantity, the source, and the factors leading to construction waste. The present study aims to find out the quantity, the source, and the factors resulting in construction waste in Gran Sungkono Langoon Project by using Pareto Method and Fish Bone Diagram. This study also aims to categorize the construction waste in Grand Sungkono Langoon Project based on its type by using Pareto Method and Fish Bone diagram. The present study employed descriptive study with qualitative analysis. It was done by analyzing and evaluating construction waste. The result of the study was in the form of data table on construction waste in structural construction using Pareto method and Fish Bone Diagram in Grand Sungkono Langoon Project. The study found that the most significant amount of material waste in Grand Sungkono Langoon project is steel bar (Rp.229.009.000), total amount of construction waste was 0.92% or equal to Rp 263.090.000 from total project cost of Rp. 24.204.280.000. The source of material waste comes from piles, casting, steelwork and formwork, and the factors resulting in construction waste were the condition of the pile, this can be caused by careless unloading process. Besides, not all piles get into the ground for its condition is different at each point. Regarding reinforcement, it turned into waste because of cutting mistake. The category of construction waste in a structural project is casting, steelwork, and formwork.